2007
DOI: 10.1017/s0003055407070554
|View full text |Cite
|
Sign up to set email alerts
|

Framing Public Opinion in Competitive Democracies

Abstract: What is the effect of democratic competition on the power of elites to frame public opinion? We address this issue first by defining the range of competitive contexts that might surround any debate over a policy issue. We then offer a theory that predicts how audiences, messages, and competitive environments interact to influence the magnitude of framing effects. These hypotheses are tested using experimental data gathered on the opinions of adults and college students toward two policy issues—the management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
587
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(629 citation statements)
references
References 41 publications
34
587
3
5
Order By: Relevance
“…Rather, some positive views will be pushed to undecided or negative and some undecided views also pushed to negative. This sort of ''backlash'' effect is consistent with research showing negative effects on opinion of weak-inapplicable frames competing with strong-applicable ones (Chong and Druckman 2007b), of distrust towards a political leader (Levi and Stoker 2000, 489-90) and of general levels of trust for citizens' negative evaluations of foreign countries (Brewer et al 2004).…”
Section: Conditional Effects Of Public Diplomacysupporting
confidence: 82%
“…Rather, some positive views will be pushed to undecided or negative and some undecided views also pushed to negative. This sort of ''backlash'' effect is consistent with research showing negative effects on opinion of weak-inapplicable frames competing with strong-applicable ones (Chong and Druckman 2007b), of distrust towards a political leader (Levi and Stoker 2000, 489-90) and of general levels of trust for citizens' negative evaluations of foreign countries (Brewer et al 2004).…”
Section: Conditional Effects Of Public Diplomacysupporting
confidence: 82%
“…As for the right hand side of the model, we created a control variable called instrumentalism that measures respondents' beliefs about the instrumental value of foreign aid: whether aid strengthens US/GB political influence and helps to prevent international terrorism. 3 Table 4 contains marginal effects from two separate probit estimations for each country.…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…However, second-generation framing research has increasingly focused on instances of when framing does (or does not) occur (Brewer, 2003(Brewer, , 2005Chong and Druckman, 2007b;Druckman, 2001aDruckman, , 2001bDruckman, , 2004Druckman and Nelson, 2003;Sniderman and Theriault, 2004). For example, scholars find that framing effects are attenuated when individuals are immersed in heterogeneous, cross-cutting social networks (Druckman and Nelson, 2003) or when the media outlet carrying a message is viewed as untrustworthy (e.g., The National Enquirer; Druckman, 2001a).…”
mentioning
confidence: 99%
“…For example, scholars find that framing effects are attenuated when individuals are immersed in heterogeneous, cross-cutting social networks (Druckman and Nelson, 2003) or when the media outlet carrying a message is viewed as untrustworthy (e.g., The National Enquirer; Druckman, 2001a). Recent work has also demonstrated that multifaceted information environments reduce framing effects in what has been called dual or competitive framing (Brewer, 2003(Brewer, , 2005Chong and Druckman, 2007b;Druckman, 2001aDruckman, , 2004Druckman and Nelson, 2003;Sniderman and Theriault, 2004; see also Zaller, 1992). Evidence has also suggested that individual-level political and psychological factors influence framing, such as motivation (Druckman and Nelson, 2003) and ability (Brewer, 2003).…”
mentioning
confidence: 99%